MAJELIS SHALAWAT: Dari Genealogi Suci, Media Baru, hingga Musikalitas Religi - Rijal, Syamsul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2020)
Some da'i/mubaligh/celebrity preachers began to emerge in Indonesia with their own distinctive style and approach. This study assumes that habaib, gus, celebrity preachers rely more on entertainment performance than oratorical competence in attracting members of the congregation (followers). The results of this study show that (1) majelis shalawat has utilized new media and technology through the internet for self-promotion; (2) the promotional power possessed by the majelis shalawat is also supported by its leaders who generally have the sacred genealogy of the Hadramaut or Walisongo; (3) Shalawat practice is carried out by combining the dimensions of spirituality and musicality so that it can attract the attention of millennial youth in urban and rural areas.